Analisis Pengaruh Service Quality dan Product Quality Terhadap Customer Loyalty (Studi Pada Konsumen Es Kristal Merek Elvano di Mojokerto) - Erik Bisri Alamsyah; Eko Budiyanto; Edho Setya Mufti (Yos Soedarso Economic Journal (YEJ), 2022)
Research has been conducted on consumer loyalty to Crystal Ice products brand Elvano in Mojokerto. The purpose of this study is to determine the process of customer loyalty, the results of which can later be used by marketers to control long-term relationships between companies and consumers that can increase company profits. This study uses a survey method. The research population is consumers who intend to be loyal to the Elvano Di Mojokerto brand Crystal Ice. Samples taken as many as 200 people. The analytical method in this study uses Structural Equation Modeling (SEM). SEM is a multivariate technique that combines aspects of multiple regression and factor analysis to estimate a series of dependency relationships simultaneously. Hypothesis testing was carried out using the AMOS program version 18 to analyze the causality relationship in the proposed structural model. Based on the results of structural model analysis, it can be seen that Service Quality affects the level of Customer Loyalty and Product Quality affects the level of Customer Loyalty.